2014
DOI: 10.1155/2014/150617
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Extracts Alleviate Aβ25–35‐Induced Injury and Change the Gene Expression Profile in PC12 Cells

Abstract: Mulberry, which contained high amounts of anthocyanins, has been used in traditional Chinese medicine. Mulberry fruit extracts (ME) have demonstrated the antioxidant activity and neuroprotection. The study was to investigate the neuroprotective efficacy of ME against β-amyloid 25–35- (Aβ 25–35-) induced PC12 cells injury. Cells preincubated with or without ME (200 μg/mL) for 24 h were treated with Aβ 25–35 (20 μmol/L) for another 24 h. Cell viability was assessed by MTT, gene expression profiles were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Mitochondria is an organelle function in ATP synthesis and Ca 2+ homeostasis, thus its impairment will provoke [Ca 2+ ] i release and the apoptotic protease-activating factor 1 (Apaf1)-mediated intrinsic apoptotic pathway. Indeed, Aβ 25-35 peptides induced Apaf1-mediated cell death, while pre-treatment with ethanolic extract of Chinese M. nigra for 24 h followed by Aβ [25][26][27][28][29][30][31][32][33][34][35] exposure downregulated Apaf1 [37]. Previous studies showed that cyanidin and kuromanin attenuate Aβ-induced PC12 neurotoxicity by maintaining mitochondrial stability [38].…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondria is an organelle function in ATP synthesis and Ca 2+ homeostasis, thus its impairment will provoke [Ca 2+ ] i release and the apoptotic protease-activating factor 1 (Apaf1)-mediated intrinsic apoptotic pathway. Indeed, Aβ 25-35 peptides induced Apaf1-mediated cell death, while pre-treatment with ethanolic extract of Chinese M. nigra for 24 h followed by Aβ [25][26][27][28][29][30][31][32][33][34][35] exposure downregulated Apaf1 [37]. Previous studies showed that cyanidin and kuromanin attenuate Aβ-induced PC12 neurotoxicity by maintaining mitochondrial stability [38].…”
Section: Discussionmentioning
confidence: 95%
“…As we previously described, ME showed a total phenolic content of 1.78% (Kim et al, 2010b) and those compounds may exert antioxidant and anti-inflammatory activities that enhance health, particularly in the brain Oh, 2012, 2013). Especially, anthocyanins which are well known to be rich in ME have been shown to modulate the progression of AD (Qin et al, 2013;Shih et al, 2010;Song et al, 2014). For example, one of the major anthocyanin in ME, cyanidin 3-O-glucoside, has improved learning and memory against Aβ toxin via modulation of GSK-3β and tau (Qin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of studies revealed multibioactive functions of mulberry, including anti-inflammatory, antioxidant, anticarcinogenic, and antiapoptotic properties (Kim et al, 2010bKim and Oh, 2013;Liu and Lin, 2012). In addition, it was recently reported that mulberry exerts neuroprotective effects in several models (e.g., Parkinson's disease, AD, cerebral ischemia, vascular dementia, and senescence-accelerated cognitive deficiency) (Kaewkaen et al, 2012;Kang et al, 2006;Kim et al, 2010b;Shih et al, 2010;Song et al, 2014), as well as neuromodulatory effects by inducing nerve growth factor (Kim and Oh, 2013).…”
mentioning
confidence: 99%
“…anti-hyperlipidemia and antiatherogenic properties in a cholesterol-fed-rabbit model [18]as well as neuroprotective effects in PC12 cells in vitro [19] and in mousebrain-injury model [20]. Also, they have anticancer effects of human lung cancer cell line A549 [21], human gastric carcinoma cell lines (SNU-601) [22] and AGS gastric cancer xenograft model cells [23].…”
Section: Introductionmentioning
confidence: 99%